A Transformerless Common-Ground Two-Switch Single-Phase Inverter for Battery Energy Storage System Applications - Assunção , Gabriel de O. (2021)
This paper proposes a transformerless common-ground single-phase inverter for battery energy storage system (BESS) applications. With regard to conventional converters operating as a voltage source inverter (VSI), the proposed converter offers the advantage of a common connection between the battery bank negative terminal and the ground. Hence, the common-mode voltage becomes continuous while common-mode currents flowing through parasitic capacitances located between the battery bank and the grounded metallic frame are eliminated, allowing operation without a transformer. This new topology has only two power semiconductors, two inductors and one capacitor, without the need for a filter on the AC grid side. The converter operation is described and the relevant equations for sizing are presented along with the main characteristics. A 1 kW non-optimized prototype was dimensioned, built and tested to validate in practice the theoretical analysis, and a maximum efficiency of 95.25% was obtained. Due to the simplicity, low number of active components, no clamping circuit requirement and the common-ground, this topology is a very interesting option for the above-mentioned application.